المعجم التعليمي: مفهومه ومواصفاته - تارش, جموعي (جامعة الوادي - university of Eloued, 2020)
تعد المعاجم التعليمية من بين المعاجم التي عرفت انتشارا واسعا في الوقت الحالي، وذلك بالنظر لما تكتسيه من أهمية في حقلي المعجمية وتعليمية اللغات معا. ولذا فالمعاجم التعليمية ضرورة فرضتها متطلبات العصر والتطور الذي شهدته المناهج التعليمية من حيث الوسائل المستخدمة المستعان بها في العملية التعليمية، وذلك لما لها من دور كبير في إثراء وإغناء الرصيد اللغوي للمتعلم وإكسابه كفاية لغوية تمكنه من استعمال اللغة بشكل صحيح وسليم. وما يلاحظ على هذا النوع من المعاجم هو تميزّها بمجموعة مواصفات وخصائص وخضوعها لمعايير ومقاييس تضبطها، من حيث المادة والحجم، والمنهج ، وطرق الشرح واستعمال الشواهد والطباعة. وهو ما يجعلها مميزة عن غيرها من المعاجم. ونهدف في هذه الورقة البحثية إلى الوقوف على المفهوم الاصطلاحي للمعجم التعليمي والمواصفات الأساسية التي يرتكز عليها أثناء تأليفه. ودوره في العملية التعليمية. Abstract: Didactic dictionary nowadays is hugely widespread, given its importance in both, lexical and didactic aspect of language. Thus, didactic dictionaries are required by the requirements of the age and the development of didactic curricula in terms of the means used in the educational process, for they play a significant role in enriching the linguistic repertoire of the learner and gaining a linguistic proficiency that enables them to use the language properly. What is remarkable about this type of dictionaries is their distinction with a set of specifications and characteristics. They are subject to criteria and measures, in terms of material, size, methodology, methods of explanation and printing, which makes them distinctive among all other dictionaries. This paper aims to identify the conventional concept of the didactic dictionary, and the basic specifications upon which it is based during its formation, along with its role in the educational process.
مقال
Keywords: Dictionary, Didactic, Concept, Industry, Specifications, learner; معجم؛ تعليمي؛ مفهوم؛ صناعة؛ مواصفات؛ متعلم.